Anatomy practical guide book for general and musculoskeletal modules / Haszianaliza Haslan ... [et al.] - Haslan, Haszianaliza; Choy, Ker Woon; Azmi, Muhammad Fairuz; Zaidun, Nurul Hannim; Adib Ridzuan, Nurul Raudzah; Syed Ahmad Fuad, Syed Baharom (UiTM Press, 2023)
General module provides fundamental knowledge on the normal structure and organization of the human body. Understanding this basic knowledge is vital in order to grasp comprehensive understanding of how the human body works and diseases that arise following various insults. The cell is a basic functional unit that is organized into four basic types of tissue, namely the epithelial, connective, muscle and nervous tissue. A collection of these tissues in various morphology and proportion formed an organ, for example the heart and stomach. Epithelial tissue is the tissue covers and lines interface surface and body cavities. It regulates exchange of molecules involves in absorption and secretion. It is characterized by: • Composed of closely aggregated polyhedral cells. • Exhibit functional and morphological polarity. • Basal surface attached to the basement membrane. • Have strong adhesion to each other.